Perancangan Prototipe Aplikasi Rekam Kesehatan Personal Pada Pasien Tuberculosis Berbasis Mobile - Desfa Anisa; Chika Nabila Franciska (BULLET : Jurnal Multidisiplin Ilmu, 2025)
Tuberculosis is a contagious disease that requires serious treatment and must also be monitored continuously. Optimal treatment requires accurate health records and the patient's health records must be easily accessible. This study aims to design a prototype of a special RKP application for patients suffering from Tuberculosis. From this design, it is expected to help patients infected with the disease so that their health conditions can be monitored, it is also expected to make it easier for health workers to see and monitor TB patients' diseases. The prototype application design is equipped with features to view patient treatment and care schedules, view patient medical records, and remind patients to take medication. The implementation of this prototype is expected to improve the quality of health services and help Tuberculosis patients manage their health independently. Currently, the use of mobile applications to monitor Tuberculosis is not very familiar among patients, although there is a significant need and benefit from this technology. Most patients realize the importance of adherence to treatment and routine care to achieve recovery. Therefore, Tuberculosis patients need support in managing their treatment schedules.